Energy Efficiency Policies in Non-Residential Buildings: the Case of the University of Bari Aldo Moro - Vera Amicarelli; Christian Bux; Giovanni Lagioia; Teodoro Gallucci (Amfiteatru Economic)
The increase in global energy consumption gives rise to several issues with regard to limited energy resources, supply difficulties and environmental impacts. The main concern is that this trend does not cease to curb its growth, while the common challenge is to reduce energy consumption, thus mitigating its impacts on climate change. In particular, Building Energy Efficiency requires particular attention, as the building sector is responsible for approximately 35% of global energy consumption. Thus, European Union policies have been interested in this field, promoting diverse actions in order to pursue and achieve sustainability across the building sector, such as the allocation of funds for restructuring and for energy refurbishment, as well as regulations and directives concerning energy certification and reduction in the consumption of natural resources. This paper has two main objectives. First, to analyze the role of the building sector at a global and European level and its contribution to climate change, highlighting the main differences between residential and non-residential buildings. Second, to present an ex-ante analysis and an expost preliminary results obtained from the energy requalification program applied to an Italian public non-residential building: the Economy Campus of the University of Bari Aldo Moro, with regard to economic (monetary cost reduction) and environmental (energy benefits and greenhouse-gases reduction) savings